Disclosure of Intellectual Capital: Evidence from Indian Annual Reports - Singhal, Soumya; Gupta, Seema; Gupta, Vijay Kumar (Public Finance Quarterly, 2022)
The shifting of the economy from manufacturing-based to knowledge-based has raised the importance of Intellectual Capital (IC) in the business value creation process. Although IC has been recognized in integrated reports, limited information about it is still reported in traditional financial disclosures. The present study examines the extent of intellectual capital disclosure (ICD) in Indian firms and assesses the gap between stakeholder expectations and industry disclosure procedures. For this purpose, content analysis has been performed on a sample of 30 non-financial firms listed on the Bombay Stock Exchange (BSE) for the year 2019–2020 by constructing a disclosure index of 42 items based on previous studies, under the three categories of IC, namely, structural capital, relational capital, and human capital. The results reveal that the overall disclosure of intellectual capital by Indian firms is low. The companies disclose only 42% of the Intellectual Capital items. Further, it is found that maximum number of companies are disclosing structural capital, while human capital disclosure obtains the minimum score. The results imply the need to develop a proper framework for reporting intangibles in the annual statements of organizations in India.